Economic consequences of population ageing in the Asia-Pacific region and the role of intergenerational support - United Nations Economic; Social Commission for Asia; the Pacific; Ronald Lee (Asia-Pacific Sustainable Development Journal, 2025)
Although some Asia-Pacific countries still experience demographic dividends, all will soon be ageing, which will slow the growth of their gross domestic product. The impact of ageing on individual welfare depends on how much older persons rely on income from assets and labour versus public and private transfers, which are vulnerable to population ageing and unsustainable as currently structured. Increased fertility would raise economic pressures for many decades before beginning to help. Costs should be shared intergenerationally, through higher taxes on workers and through both later retirement and more asset accumulation which would reduce the need for transfers in the future.